Ancestral state reconstruction infers phytopathogenic origins of sooty blotch and flyspeck fungi on apple - Ismail, Siti Izera; Batzer, Jean Carlson; Harrington, Thomas C.; Crous, Pedro W.; Lavrov, Dennis V.; Li, Huanyu; Gleason, Mark L. (Mycological Society of America, 2015)
Members of the sooty blotch and flyspeck (SBFS) complex are epiphytic fungi in the Ascomycota that cause economically damaging blemishes of apples worldwide. SBFS fungi are polyphyletic, but approx. 96% of SBFS species are in the Capnodiales. Evolutionary origins of SBFS fungi remain unclear, so we attempted to infer their origins by means of ancestral state reconstruction on a phylogenetic tree built utilizing genes for the nuc 28S rDNA (approx. 830 bp from near the 59 end) and the second largest subunit of RNA polymerase II (RPB2). The analyzed taxa included the well-known genera of SBFS as well as non-SBFS fungi from seven families within the Capnodiales. The non-SBFS taxa were selected based on their distinct ecological niches, including plant-parasitic and saprophytic species. The phylogenetic analyses revealed that most SBFS species in the Capnodiales are closely related to plant-parasitic fungi. Ancestral state reconstruction provided strong evidence that plant-parasitic fungi were the ancestors of the major SBFS lineages. Knowledge gained from this study may help to better understand the ecology and evolution of epiphytic fungi.